Twórczość Innego – nowa wartość w sztuce i w społeczeństwie? - Nieduziak, Edyta (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2018)
This article deals with the issues of creativity of people with disabilities and their social values. The starting point is the category of Another as saturated with pejorative meanings – in a social but positive context in the study of creativity. The combination of these contradictory approaches is reflected in the art brut, represented by artists with mental incompetence. Their creativity dictated by internal compulsion is presented as the work of marginalized people. The social context, as well as the type of disability that determines the way in which this art is treated: from the rejection of, for example, the early time of Nikifor's works, to the complete recognition of, for example, F. Kahlo's painting. The basic question, however, comes down to the question of the value of this art for man. Referring to the philosophy of E. Levinas, the author seeks to show that despite the assumption of the unknowability of another human being, the greatest value of the Other art is the ability to experience, to see though a fragment of the world of artists determined by the disability.